2015
DOI: 10.1080/17482798.2015.997108
|View full text |Cite
|
Sign up to set email alerts
|

Parental Mediation of Children's Television and Video Game use in Germany: Active and Embedded in Family Processes

Abstract: In a survey study, 158 dyads of German parents and their nine to 12 year-old children reported on their television and video game consumption, parental mediation strategies, and family climate. Parents also reported their beliefs concerning media effects. We found that mediation strategies differ from acknowledged media usage conceptions in that parents play a more active role than previously assumed. Restrictive mediation comprises rules and restrictions, but also parents' educative explanations that media do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 37 publications
0
16
0
3
Order By: Relevance
“…Within the home, we might assume that parents are naturally in charge of cyber-security. After all, parents guide their children toward the most age-appropriate television programs to watch and video games to play (Nikken and Schols, 2015;Schaan and Melzer, 2015), and mediate their children's use of the internet (Livingstone and Helsper, 2008). Parenting styles, in terms of patterns or combinations of parenting practices (Darling and Steinberg, 1993) may influence the type of approach adopted by parents in their management of household cyber-security.…”
Section: Introductionmentioning
confidence: 99%
“…Within the home, we might assume that parents are naturally in charge of cyber-security. After all, parents guide their children toward the most age-appropriate television programs to watch and video games to play (Nikken and Schols, 2015;Schaan and Melzer, 2015), and mediate their children's use of the internet (Livingstone and Helsper, 2008). Parenting styles, in terms of patterns or combinations of parenting practices (Darling and Steinberg, 1993) may influence the type of approach adopted by parents in their management of household cyber-security.…”
Section: Introductionmentioning
confidence: 99%
“…Under this mediation, parents spend quality time using media simultaneously with their children while communicating with their children about the negative impact and appropriate use of media (Livingstone & Helsper, 2008). Schaan and Melzer (2015) explained that the form of active co-use (active-emotional co-use) increases family ties through inter-generational interactions, which then pose the possibility of being a protective or resilience factor reducing the probability of problematic child behavior when they face challenging social situations. This can be related to reducing the risk of peer problems and promoting prosocial behavior among children.…”
Section: Discussionmentioning
confidence: 99%
“…Parents employ restriction frequently across various media (An & Lee, 2010; Nikken & Jansz, 2006; Nikken, Jansz, & Schouwstra, 2007; Padilla‐Walker et al, 2016; Schaan & Melzer, 2015; Valkenburg et al, 1999; Warren, 2001), and for games in particular. Schaan and Melzer (2015) found that parents employed varied approaches to mediate their children's interactions with television, but primarily regulated video games through restrictive means. The authors suggested that parents may feel limited in their potential to employ active mediation or coviewing effectively, given a lack of familiarity with digital technologies.…”
Section: Parental Mediationmentioning
confidence: 99%